Linear Parameter-Varying Versus Linear Time-Invariant Reduced-Order Controller Design for Turboprop Aircraft Dynamics - Widowati, Widowati; Riyanto, Bambang; Muhammad, Hari (ITB Journal Publisher, LPPM ITB, 2012)
TheÂ applicabilityÂ ofÂ parameter-varyingÂ reduced-orderÂ controllersÂ to aircraftÂ modelsÂ isÂ proposed.Â AÂ generalizationÂ ofÂ theÂ balancedÂ singular perturbation method of the linear time-invariant (LTI) system was used to reduce the order ofÂ theÂ linear parameter-varying (LPV) system. Based on the reducedorder model, aÂ low-orderÂ LPVÂ controllerÂ wasÂ designedÂ usingÂ the Hâ synthesis technique.Â TheÂ performanceÂ ofÂ theÂ reduced-orderÂ controllerÂ wasÂ examinedÂ by applyingÂ itÂ toÂ theÂ lateral-directionalÂ controlÂ ofÂ aÂ 20th-orderÂ aircraftÂ model. Furthermore, the time responses of the closed-loop system withÂ several reducedorder LPV controllers andÂ aÂ reduced-order LTI controllerÂ wereÂ compared.Â The simulation resultsÂ show that anÂ ,Â 8th -order LPV controller can maintain stability andÂ provideÂ theÂ sameÂ levelÂ ofÂ closed-loopÂ systemÂ performanceÂ asÂ aÂ full-order LPVÂ controller.Â ThisÂ wasÂ notÂ theÂ caseÂ withÂ theÂ reduced-orderÂ LTIÂ controller, whichÂ cannotÂ maintainÂ stabilityÂ andÂ performanceÂ forÂ allÂ allowableÂ parameter trajectories.